2009
DOI: 10.2903/j.efsa.2009.1011
|View full text |Cite
|
Sign up to set email alerts
|

Species‐specific welfare aspects of the main systems of stunning and killing of farmed Atlantic Salmon

Abstract: SUMMARYFollowing a request from the European Commission, the Panel on Animal Health and Welfare was asked to deliver a scientific opinion on welfare aspect of the main systems of stunning and killing of farmed Atlantic salmon (Salmo salar) in the EU.Harvesting and processing of farmed Atlantic salmon are the same as for sea-farmed rainbow trout (Oncorhynchus mykiss); therefore this scientific opinion and its conclusions can also be applied to the sea farmed trout 1 production.A semi-quantitative risk assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Electrical stunning has the potential to rapidly induce unconsciousness in fish. Consistent with welfare recommendations [1,10,11], it has been shown that Atlantic salmon ( Salmo salar ) [12] can be rendered unconscious using a stun of 0.5 s duration. Effective 1 s stun durations have also been validated for a diverse range of freshwater and marine species [1322] including the small pelagic Atlantic herring ( Clupea harengus ) [23].…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Electrical stunning has the potential to rapidly induce unconsciousness in fish. Consistent with welfare recommendations [1,10,11], it has been shown that Atlantic salmon ( Salmo salar ) [12] can be rendered unconscious using a stun of 0.5 s duration. Effective 1 s stun durations have also been validated for a diverse range of freshwater and marine species [1322] including the small pelagic Atlantic herring ( Clupea harengus ) [23].…”
Section: Introductionmentioning
confidence: 62%
“…To ensure good welfare, death must be induced prior to consciousness recovery [1,10]. A variety of post electrical stunning slaughter methods have been investigated to date [2,12,17,20,22], including chilling by the use of cold water/ice slurries.…”
Section: Introductionmentioning
confidence: 99%
“…EFSA (EFSA AHAW Panel, 2009) assessed the welfare aspects of killing farmed Atlantic salmon and reported that pre-slaughter crowding and pumping would subject the fish to metabolic and handling stress. There is also always a certain risk of poor welfare involved when live fish are transported.…”
Section: Article 7(e)(ii) the Societal Acceptance Of Disease Preventi...mentioning
confidence: 99%